Foot Exercise and Related Outcomes in Patient With Diabetes Mellitus: A Literature Review - Dee, Theodehild M. Theresia; Fiah, Fransita M.A.; Pandie, Fance R. (International Journal of Nursing and Health Services (IJNHS), 2022)
Background: Diabetic foot ulcer is one of the most common complications in patients with diabetes mellitus. The incidence of diabetes foot ulcers affects morbidity, mortality, and financing. Foot exercise is one of the recommendations for a patient with diabetes to prevent dan accelerate the healing of the diabetic wound. Objective: This paper aims to review the literature on foot exercise and its effect. Method: A literature review was conducted in this study. Search literature used predefined keywords through several databases, namely Scopus, ProQuest, PubMed, and CINAHL. The selection of journals is based on the inclusion and exclusion criteria. Results: Seven articles met the inclusion criteria. The review showed the effect of foot exercise on diabetic foot ulcer risk factors, wound healing, and recurrence of ulcers. Recommendation: Foot exercise can be used as an option for the patient with diabetes mellitus to prevent or treat the complications related to diabetic foot ulcers